ANALISIS IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) TERHADAP KUALITAS LAPORAN KEUANGAN SKPD (STUDI KASUS PADA DINAS PPKAD KABUPATEN MINAHASA TENGGARA) - Ole, Halens Ryanlie (Universitas Sam Ratulangi, 2014)
The purpose of this study was to obtain how to implementation of the Regional Management Information System (SIMDA) on the quality of financial reporting in the Agency of Revenue, Finance and Asset Management (DPPKAD) of Southeast Minahasa Regency. This research method is qualitative research Â with interviews and document study taken with cross-sectional approach. Interviews performed to Southeast Minahasa District Secretary about SIMDA implementation and the survey of preparation of financial statements in DPPKAD to five respondents and in SKPD to 30 treasurers. The results reveal that the use of the SIMDA process in accordance with the mandate Minister Regulation No. 13 of 2006 on Regional Financial Management Guidelines. The SKPD participation rate is is still low, but participation by type of user has been pretty good . The data show that opinion of BPK is directly proportional to the increase in the use of SIMDA in the each of SKPD. Factors found to influence besides SIMDA to the quality of the financial statements is the human factor, the inspectorate, head of Regional leadership, feedback on BPK recommendations, and consistency in the application of SIMDA. Evaluations on human factors concluded that the level of human resources were classified based on aspects SIMDA educational background and the number of Bimtek. Inspectorate human resources is very good in quality but less in number in serving on SKPD. Local leaders considered quite good, the feedback of the BPK recommendation is quite good, and consistency in the application of SIMDA also been good.